THE FUNCTIONS OF VERB PHRASE IN WESTLIFE’S SONG LYRICS - Ismarini Hutabarat; Maria Merliani Gorat (LPPM Universitas Darma Agung, 2021)
This thesis dealt with Verb Phrase in Westlife’s Song Lyrics. Verb phrase was an important part of a sentence. It was important to make a study about verb phrase. The data in this study were seven songs of Westlife from their album, The World of Our Own. The song lyrics were analyzed to find out the types of verb phrase, the functions of verb phrase and the meaning of auxiliary in the verb phrase found in Westlife’s song lyrics. The method used in this study was descriptive qualitative method. The results of the study showed that the functions of the verb phrases in Westlife’s song lyrics were as predicates, as noun phrases modifiers, adjective phrase complements, and verb phrase complements.